Inventory Performance Related to Financial Performance? A Case Study in Manufacturing Sector - Chen, Chih Hsuan (2011)
This study is to investigate the importance of inventory and the correlation to financial performance. The competitive marketplace has driven the supply chain environment complex and uncertain customer demand. The delivery speed is one of the significant factors to reach customer requirements in the manufacturing sector. The inability of delivering on time may cause the loss of business opportunities. Moreover, the inventory is a double edge sword to manufacturers, advantages and disadvantages appeared whether holding inventory or not.